Вербализованный эквивалент концепта "познание" - Нижегородцева-Кириченко, Лариса; Ніжегородцева-Кириченко, Лариса (Східноєвропейський національний університет імені Лесі Українки, 2014)
В фокусе внимания находится вербализованный концепт ПОЗНАНИЕ (COGNIZANCE). Теоретическая часть посвящена краткому экскурсу лингво-когнитивных рассуждений относительно понимания процесса познания. В статье также кратко освещаются философский, психологический и лингвистический аспекты основных подходов к изучению роли познания. Определены причины, обусловливающие необходимость изучения взаимосвязи “связи языка и познания”. Обращено внимание на тезаурусную распаковку вербализованного концепта ПОЗНАНИЕ. Статья касается также универсального лингвистического феномена синонимии, который рассматривается с позиций когнитивной лингвистики. Методологической базой рассмотрения процессов синонимии является презентация семантических связей в рамках фреймовой теории,при этом затрагивается аспект прототипических концептов, входящих в орбиту интеллектуальной деятельности. В результате практического концептуального анализа построены синонимические схемы. The focus of the article is a verbalized concept COGNIZANCE. The theoretical part is devoted to a brief excursus of linguistic and cognitive reasoning regarding the understanding of the process of cognition. Attention has been devoted to the origin of this concept. The article also briefly discusses the philosophical, psychological and linguistic aspects of the main approaches to the study of the role of cognition. The reasons for the necessity of examining the relationship between language and cognition have been identified. Attention is paid to the thesaurus unpacking the verbalized concept of COGNIZANCE. The article also applies to the universal linguistic phenomenon of synonymy, which is viewed from the standpoint of cognitive linguistics. Methodological basis to consider the processes of synonymy is the presentation of semantic relationships within the framing theory. At the same time the aspects of prototypical concepts included in the orbit of intellectual activity are taken under consideration. As a result of practical conceptual analysis synonymous schemes have been built.
Вербалізований еквівалент концепту ПІЗНАННЯ.
Keywords: вербализованный концепт; интеллектуальная деятельность; познание; когнитивная лингвистика; фреймовые структуры; вербалізований концепт; інтелектуальна діяльність; когнітивна лінгвістика; фреймові структури